Implementasi Manajemen Organisasi di Stais Al-Ishlahiyah Binjai - Mesiono Mesiono; Arie Dwi Ningsih; Rosida Hanum; Desy Ariani (Departement of Mathematics Education, 2023)
Every college has a goal. To achieve this goal, higher education institutions need a good organizational structure, namely a healthy and efficient organizational structure. organizational structure is the result of the management process, in this case as the output of the organizing process. In the process of establishing the organizational structure, the Team must pay attention to and apply various organizational principles, namely the formulation of clear goals, departmentalization, division of labor, delegation of authority, span of control, organizational levels, and unity of command. The application of these principles in the organizational process can produce a sound and efficient organizational structure. Quality tertiary education plays an important role in nation-building, it is a means to give birth to educated-intellectuals. The number of educated people produced by universities has accelerated the improvement of the quality of people's lives in this country. Universities are obliged to provide a quality educational process. From that, thinkers, initiators and implementers will be born in various fields of community life. This research uses a qualitative approach with a case study type with a multi-case design. Collecting data through observation, interviews and documentation. Data analysis using the Miles and Huberman data analysis model which includes four components, namely data collection, data reduction, data presentation and drawing conclusions. Checking the wetness of the data using triangulation. Now, educational institutions are focused on the era a very big and undeniable transformation that universities must accept if they want to survive, struggle, and develop. Solving the problem, many ideas are explored, such as the concept of economy and decentralization.